Relative tidal volume and respiratory airflow estimation using tracheal sound and movement during sleep. (3rd February 2021) - Montazeri Ghahjaverestan, Nasim; Kabir, Muammar M.; Saha, Shumit; Gavrilovic, Bojan; Zhu, Kaiyin; Taati, Babak; Alshaer, Hisham; Yadollahi, Azadeh
Summary: Airflow is the reference signal to assess sleep respiratory disorders, such as sleep apnea. Previous studies estimated airflow using tracheal sounds in short segments with specific airflow rates, while requiring calibration or a few breaths for tuning the relationship between sound energy and airflow. Airflow−sound relationship can change by posture, sleep stage and airflow rate or tidal volume. We investigated the possibility of estimating surrogates of tidal volume without calibration in the adult sleep apnea population using tracheal sounds and movements. Two surrogates of tidal volume: thoracoabdominal range of sum movement and airflow level were estimated. Linear regression was used to estimate thoracoabdominal range of sum movement from sound energy and the range of movements. The sound energy lower envelope was found to correlate with airflow level. The agreement between reference and estimated signals was assessed by repeated‐measure correlation analysis. The estimated tidal volumes were used to estimate the airflow signal. Sixty‐one participants (30 females, age: 51 ± 16 years, body mass index: 29.5 ± 6.4 kg m −2, and apnoea−hypopnea index: 20.2 ± 21.2) were included. Reference and estimated thoracoabdominal range of sum movement of whole night data were significantly correlated with the reference signal extracted from polysomnography (r = 0.5 ± 0.06). Similarly, significant correlations (r = 0.3 ± 0.05) were found for airflow level. Significant differences in estimated surrogates of tidal volume were found between normal breathing and apnea/hypopnea. Surrogate of airflow can be extracted from tracheal sounds and movements, which can be used for assessing the severity of sleep apnea and even phenotyping sleep apnea patients based on the estimated airflow shape.